The The Effect of E-Service Quality Through Customer Satisfaction and Customer Trust on Customer Loyalty of Klikindomaret Users - Agritika, Dayinta Fitriani; Hartoyo; Suharjo, Budi (School of Business, IPB University (SB-IPB), 2024)
A change in consumer behavior that increasingly uses digital systems in shopping encourages companies to implement an omnichannel sales system, as well as Indomaret. Meanwhile, the increasing number of retailers adopting the online system will lead to the emergence of competition between sellers, so customer loyalty has an important role. In running a business online, service quality is known to influence customer satisfaction and customer shopping behavior. This study aims to analyze the effect of e-service quality on customer loyalty in using Klik Indomaret. This research was conducted on 350 respondents who had used Klik Indomaret for the last six months and were domiciled in Jabodetabek. Data was collected using a snowball sampling technique with a questionnaire distributed online. The method used in this research is structural equation modeling (SEM). The results of the study show that e-service quality has a significant direct effect on customer satisfaction and trust. Furthermore, customer satisfaction also has a significant direct effect on customer trust. Increasing customer satisfaction and trust will also increase customer loyalty in shopping through Klik Indomaret. Managerial implications that can be applied by companies to increase customer loyalty include improving KlikIndomaret's e-service quality so that customer satisfaction and trust in e-commerce increase. In addition, the majority of KlikIndomaret's customers are Generation Z and millennials, so information and promotions will be delivered more effectively through message services and social media by using digital marketing. Keywords: customer loyalty, customer satisfaction, customer trust, e-service quality, SEM